Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In triangle inscribed circle with radius $r = 1$ and one of it sides $a=3$. Find the minimum area of triangle? Ans = 5.4

My reasonings:

enter image description here

$BC = a$, $AC = b$, $AB = c$




$a=z+y$, $b=x+y$, $c=x+z$

The radius of the incircle is $$r =\frac{A_{ABC}}{s}$$ where $s = \frac{a+b+c}{2} = x + y+ z$. By condition $z+y=3$ so $s=x+3$

By Heron's formula, the area of the triangle is $A=\sqrt{s(s-a)(s-b)(s-c)}$

In other side $A=sr = x+3$.

What is next? I think that I should get a fucntion for which I will can find a minimum, but I don't know how.

share|cite|improve this question
If you can prove that the least area occurs when side $a$ is the base of an isosceles triangle then you are done. – RicardoCruz Mar 25 '14 at 3:43
@RicardoCruz Isnt that case for the maximum area? – Sawarnik Mar 26 '14 at 9:43
up vote 5 down vote accepted

You were on the right track.
Using your notation, $A = \sqrt{s(s - a)(s - b)(s - c)} = \sqrt{(x + 3)xyz}$, but also $A = x + 3$. So $$\begin{align} \sqrt{(x + 3)xyz} &= x + 3, \\ xyz &= x + 3, \\ x &= \frac{3}{yz - 1}. \end{align}$$

Substituting that into $A$ we get $$A = \sqrt{\left(\frac{3}{yz - 1} + 3\right)\frac{3}{yz - 1}yz} = \sqrt{\frac{3yz}{yz - 1}\cdot\frac{3}{yz - 1}yz} = \frac{3yz}{yz - 1} = \frac{3}{yz - 1} + 3.$$

Finally, by AM-GM we get lower bound: $$A = \frac{3}{yz - 1} + 3 \geqslant \frac{3}{\frac{(y + z)^2}{4} - 1} + 3 = \frac{3}{\frac{9}{4} - 1} + 3 = \frac{12}{5} + 3 = \frac{27}{5} = 5.4$$

Because it is AM-GM, equality is reached when $y = z = 1.5$

P.S. You may wonder, why for some values of $y$ and $z$ expression $\frac{3}{yz - 1}$ may become infinite or negative. Isn't it strange? Besides, I myself silently assumed that it is positive. And there's a reason for that.
Positive values of $\frac{3}{yz - 1}$ correspond to the situation you describe: a circle inscribe in a triangle.
When it becomes infinite two sides $AB$ and $AC$ become parallel.
And finally, when it's negative, your circle is no longer an incircle, it becomes excircle.

share|cite|improve this answer
Thank you. But can you explain last part yours solving? How do you get $\frac{(y+z)^2}{4} - 1$ in right side in denominator? – Alexander Side Mar 27 '14 at 12:50
@AlexanderSide AM-GM looks like $\sqrt{yz} \leqslant \frac{y+z}{2}$. Starting from there we get $$\begin{align} yz &\leqslant \left(\frac{y+z}{2}\right)^2 = \frac{(y+z)^2}{4}, \\ yz-1 &\leqslant \frac{(y+z)^2}{4} -1, \\ \frac{3}{yz-1} &\geqslant \frac{3}{\frac{(y+z)^2}{4} - 1}. \end{align}$$ – ElThor Mar 27 '14 at 13:36

Trigonometric approach:

In your notation,

$AD=AF=x$, $FC=CE=y$, $BD=BE=z$,

denote in addition

$\alpha=\angle OAF=\angle OAD$, $~~~\beta=\angle OCF=\angle OCE$, $~~~\gamma=\angle OBE=\angle OBD$.

So, if $r=1$, then $x=\dfrac{1}{\tan\alpha}$, $~~~y=\dfrac{1}{\tan\beta}$, $~~~z=\dfrac{1}{\tan\gamma}$.

Then, as you said, $$ A=r(x+y+z)=r(x+3)=x+3. $$

$$ x = \dfrac{1}{\tan(90^\circ - \beta-\gamma)} = \tan(\beta+\gamma) = \dfrac{\tan\beta+\tan\gamma}{1-\tan\beta\tan\gamma}. $$ Dividing numerator and denominator by $(\tan\beta\tan\gamma)$, we get: $$ x=\frac{z+y}{yz-1}=\frac{3}{yz-1}. $$

$$ A=x+3=\frac{3}{yz-1}+3. $$

Further thoughts - as in answer of ElThor.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.